2019
DOI: 10.1371/journal.pone.0209985
|View full text |Cite
|
Sign up to set email alerts
|

Women’s reproductive health decision-making: A multi-country analysis of demographic and health surveys in sub-Saharan Africa

Abstract: IntroductionWomen’s ability to make decisions regarding their reproductive health has important implications for their health and well-being. We studied the socio-demographic factors affecting reproductive health decision-making among women in 27 sub-Sahara African countries.Materials and methodsThe study made use of pooled data from current Demographic and Health Survey (DHS) conducted from January 1, 2010 and December 31, 2016 in 27 countries in sub-Sahara African. Binary and multivariate logistic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
84
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 18 publications
18
84
1
2
Order By: Relevance
“…In the decision-making process, demographic characteristics, women's education, spouse's education, occupation, and property present the potential to influence informed decision making. This process can also be affected by characteristics such as religion, place of origin, and cultural practices [14]. Because structural determinants refer to political, social, and economic issues, they also cover social and economic statuses [14,43], which influence the use of health facilities [44].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the decision-making process, demographic characteristics, women's education, spouse's education, occupation, and property present the potential to influence informed decision making. This process can also be affected by characteristics such as religion, place of origin, and cultural practices [14]. Because structural determinants refer to political, social, and economic issues, they also cover social and economic statuses [14,43], which influence the use of health facilities [44].…”
Section: Discussionmentioning
confidence: 99%
“…This process can also be affected by characteristics such as religion, place of origin, and cultural practices [14]. Because structural determinants refer to political, social, and economic issues, they also cover social and economic statuses [14,43], which influence the use of health facilities [44]. Employment status, education level, and income are the most important indicators [45], which were also introduced at the Cairo Conference as facilitators of empowering women in health issues [46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though, studies have revealed the in uence of socio-demographic, marital and psychological factors, gender norms, and women's position within the household as well as community factors on women's ability to negotiate sex in many parts of the globe has been examined [35,[51][52][53]. Other studies considered condom use and sexual negotiation among young men and women [54]; women's household decision-making autonomy and safer sex negotiation [55]; women's decision-making about self-protection during sexual activity [56]; household decisionmaking among married women [57] and women's reproductive health decision-making [58]. Despite the governmental and non-governmental efforts to minimize new infections in most countries with generalized or high burden epidemics, including Nigeria, the comparison and measurement of the interaction in uence of family structure and decision-making autonomy on attitudes towards negotiating safe sexual practices has been quite limited.…”
Section: Introductionmentioning
confidence: 99%